2007
DOI: 10.1016/j.amjmed.2007.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial to Improve Fracture Prevention in Nursing Home Residents

Abstract: BACKGROUND-Interventions to improve the fracture prevention in nursing homes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 25 publications
1
50
0
Order By: Relevance
“…In light of this evidence and results from other studies[6, 7], we believe that evidence implementation needs to be a three-pronged approach involving not just the physician and healthcare providers, but also must consider the system and patient factors.…”
Section: Clinical and Translational Research As It Applies To Qualitymentioning
confidence: 90%
“…In light of this evidence and results from other studies[6, 7], we believe that evidence implementation needs to be a three-pronged approach involving not just the physician and healthcare providers, but also must consider the system and patient factors.…”
Section: Clinical and Translational Research As It Applies To Qualitymentioning
confidence: 90%
“…To evaluate the effect on osteoporosis management of group practice setting and an individual physician's proclivity to treat his or her patients similarly, we used datasets from two separate randomized, controlled studies of osteoporosis quality improvement interventions(2, 3, 8, 9). The GIOP dataset included information for 6,281 long term glucocorticoid users enrolled in a large U.S. healthcare organization.…”
Section: Methodsmentioning
confidence: 99%
“…Using data from two previously published studies of osteoporosis management in long term glucocorticoid users (GIOP dataset) and nursing home patients with known osteoporosis or prior fracture (SPOF dataset) (2, 3, 8, 9), we evaluated whether there was significant similarity in osteoporosis management between physicians who practiced within the same outpatient group, or within the same nursing home. We tested the hypothesis that prior to any intervention and after controlling for patient factors (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Some of the potential causes for this treatment gap include limited access to diagnostic methods for fractures and BMD, lack of knowledge about evidence-based interventions for osteoporosis in RACFs, assumptions about length of stay and survival, and family and patients' concerns about polypharmacy and potential side effects. 8 Nevertheless, hip fractures in institutionalized older adults constitute an important cause of morbidity and mortality that could be prevented with an appropriate evidence-based approach to prevention.…”
Section: Fracture Preventionmentioning
confidence: 99%
“…A randomized trial to improve fracture prevention in nursing home residents demonstrated that audit feedback and education interventions are ineffective in improving fracture prevention. 28 In this study, nursing homes (n = 67) with >or = 10 residents with a diagnosis of osteoporosis or recent hip fracture (n = 606) were randomized to receive an early or delayed intervention consisting of audit and feedback, educational modules, teleconferences, and academic detailing. Medical record abstraction and the Minimum Data Set were used to measure the prescription of osteoporosis therapies before and after the intervention period, with no significant improvements being observed in any of the quality indicators.…”
Section: Fracture Preventionmentioning
confidence: 99%